Optimization of Digital-Based Marketing Strategies to Enhance Public Interest in Islamic Financial Products - Nurhaliza, Elsa; Pitri, Alisyah; Fatimah, Siti; Nilfatri; Okva Marwendi, Reza; Khoiratun Nisak, Sayida (CV. Civiliza Publishing, 2025)
This study analyzes the marketing strategies employed by Koperasi Insan Madani Syariah to enhance public interest and trust in Sharia-based financial products in Geragai District, as well as the challenges faced in their implementation. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and documentation involving cooperative management, members, and the target community. Findings reveal that the cooperative applies a Sharia-compliant marketing mix (4Ps) comprising halal and transparent products, direct community outreach through socio-religious approaches, and educational promotion grounded in religious values. These strategies effectively build trust and member loyalty. However, obstacles such as low Islamic financial literacy, competition from conventional institutions, limited human resources, and negative perceptions of cooperatives persist. The study highlights the novelty of integrating spiritual values, justice, and ukhuwah within marketing efforts, with education serving as a critical foundation for success. The research implies the necessity of inclusive financial education, improved risk management, and collaboration with religious institutions to sustainably enhance public trust and competitiveness of Sharia cooperatives in the evolving financial landscape